The new Blackwell companion to social theory - Turner, Bryan S. (Blackwell companions to sociology, 2009)
"A comprehensive new collection covering the principal traditions and critical contemporary issues of social theory. Builds on the success of The Blackwell Companion to Social Theory, second edition with substantial revisions, entirely new contributions, and a fresh editorial direction. Explores contemporary areas such as actor network theory, social constructionism, human rights and cosmopolitanism. Includes chapters on demography, science and technology studies, and genetics and social theory. Emphasizes key areas of sociology which have had an important impact in shaping the discipline as a whole"--